Bartonella spp. e o risco potencial de transmissão por transfusão sanguínea : Bartonella spp. and the potential risk of transmission by blood transfusion - Pitassi, Luiza Helena Urso, 1971- (2013)
Orientador: Paulo Eduardo Neves Ferreira Velho